2010
DOI: 10.1002/eji.200939455
|View full text |Cite
|
Sign up to set email alerts
|

Murine visceral leishmaniasis: IgM and polyclonal B‐cell activation lead to disease exacerbation

Abstract: In visceral leishmaniasis, the draining LN (DLN) is the initial site for colonization and establishment of infection after intradermal transmission by the sand fly vector; however, little is known about the developing immune response within this site. Using an intradermal infection model, which allows for parasite visceralization, we have examined the ongoing immune responses in the DLN of BALB/c mice infected with Leishmania infantum. Although not unexpected, at early times post-infection there is a marked B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 61 publications
(102 reference statements)
6
84
1
1
Order By: Relevance
“…The results from this protocol were initially hampered by relatively higher titers of antigen-specific antibodies, especially IgM and IgG2b isotypes, in the preimmunization serum samples (data not shown), possibly caused by environmental exposure to ovalbumin in feed or bedding. A similar polyclonal antiovalbumin response was seen in unimmunized BALB/c mice infected with Leishmania infantum (37). After the third immunization, each LPS preparation tested increased the titers of the complement-fixing, Th1-associated isotype IgG2a in most vaccinated mice (Fig.…”
Section: Naturally Occurring Lt-lps Preparations Promote a Balanced Isupporting
confidence: 68%
“…The results from this protocol were initially hampered by relatively higher titers of antigen-specific antibodies, especially IgM and IgG2b isotypes, in the preimmunization serum samples (data not shown), possibly caused by environmental exposure to ovalbumin in feed or bedding. A similar polyclonal antiovalbumin response was seen in unimmunized BALB/c mice infected with Leishmania infantum (37). After the third immunization, each LPS preparation tested increased the titers of the complement-fixing, Th1-associated isotype IgG2a in most vaccinated mice (Fig.…”
Section: Naturally Occurring Lt-lps Preparations Promote a Balanced Isupporting
confidence: 68%
“…It is known that B cells exacerbate Leishmania infections (5,(18)(19)(20). B cell-deficient (mMT) mice are indeed more resistant than WT mice to infection with L. donovani (see Supplemental -restricted CD8 T cell epitope of OVA 257-264 , were adoptively transferred into mMT mice.…”
Section: B Cell Deficiency Results In Enhanced Cd8 and Cd4 Effector Fmentioning
confidence: 99%
“…Various studies have now demonstrated that B cells play a negative role in several experimental models of leishmaniasis (5,(18)(19)(20). B cell depletion was shown to enhance resistance to Leishmania tropica and Leishmania mexicana in BALB/c mice (18), and cotransfer of B cells converts T cell-reconstituted, Leishmania major-resistant, C.B-17 scid mice into a susceptible phenotype (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B cell-derived IL-10 was shown to suppress protective T cells responses and increase disease susceptibility (85). B cells are known to play a detrimental role during VL (86), not only by secreting IL-10 but also for their excessive antibody production (87). Indeed, hypergammaglobulinemia is a hallmark of VL.…”
Section: Protozoan Parasites and Ifn-imentioning
confidence: 99%